THE IMPORTANCE OF PINK OCTOBER CAMPAIGN ON BREAST CANCER AWARENESS IN BRAZIL: EVIDENCE BASED ON GOOGLE TRENDS - Silva, Antonio Márcio Teodoro Cordeiro; Leão-Cordeiro, Jacqueline Andréia Bernardes; Vilanova-Costa, Cesar Augusto Sam Tiago; Ataides, Fábio Silvestre; Sousa, Liliane Emilly dos Santos (Mastology, 2021)
Objectives: To assess the magnitude of the international movement “Pink October” in Google Search and YouTube, using the Google Trends tool. Methodology: Analyses were carried out using the Google Trends tool on Google Search and YouTube, applying the descriptor “Breast Cancer,” both in English and Portuguese. Trends data were indexed from 0 to 100, where 0 is no search on the topic and 100 represents the maximum search interest for the selected period and location. Duplicate searches, repeated by the same person, were eliminated in the Google Trends statistic. Results: Billions of searches are performed on the Google Search and YouTube per day, and by evaluating these data, Trends can be considered one of the largest real-time data sets in the world. Examining what people search for provides a unique perspective on what they are currently interested and curious about. Throughout 2019, except for the month of October, the descriptor “breast cancer” had an average search popularity of 25 points, with a range of 18 to 46 points. However, searches for the descriptor “breast cancer” intensified substantially on October. In Google Search category, searches peaked (100 points) between October 20 and 26, while on YouTube, the peak was reached on October 13 to 19, 2019. In a time range, on August 22, 2019, the interest was 38 points; on August 29, 2019, it jumped to 82 points, reaching its maximum peak of interest on September 20, 2019; and finally, on November 3, 2019, it dropped to 46 points. These data were collected at the national level, but the same trends are perceived worldwide. Conclusion: Using Google Trends, evaluation was possible to perceive the importance of Pink October Campaign to encourage the population to actively participate in the fight against breast cancer, influencing the search for information about in Google Search and YouTube, thus fulfilling one of its purposes.